Information 2.0 new models of information production, distribution and consumption - De Saulles, Martin (Facet, 2012)
"Covering every aspect of the new digital information environment from iPads and e-books to the future of information and how it will be controlled, this landmark textbook provides a comprehensive and cutting-edge guide to what's happening, why and how information professionals can have a pivotal role in this new landscape. Drawing on international case studies and current trends it explores the fundamental changes in the four core areas of information production, storage, distribution and consumption, grappling with cutting-edge issues such as: key information trends in the last 15 years such as mass broadband; the rise of grass roots information production in social media, open access publishing and the storage of information in the cloud; how informal, digital methods of information distribution like RSS and webcasting are threatening traditional stakeholders like libraries, publishers and newspapers; the reconfiguration of the relationships between software, hardware and content creation companies; and, the need for a new information literacy and the pivotal role of the information professional." -- Publisher's description.